Use of an environmental diagnostic study on a coastal lagoon as a decision support tool for environmental management policies in a coastal zone. Issue 1 (13th January 2020) - Morais, Pollyana C.V.; Lima, Marcielly F.B.; Martins, Davi A.; Fontenele, Lysandra G.; Lima, Joyce L.R.; da Silva, Ícaro Breno; Pinheiro, Lidriana S.; Nascimento, Ronaldo F.; Cavalcante, Rivelino M.; Marques, Elissandra V.
Abstract : Purpose: An efficient and adequate environmental monitoring plan is essential to any integrated coastal zone management (ICZM) program. The purpose of this paper is to apply an environmental diagnostic study to a coastal lagoon using anthropogenic markers as a decision support tool to aid the development of coastal environmental management policies. Design/methodology/approach: Specifically, environmental status and anthropogenic sources were determined as part of a coastal environmental management plan; a study of human occupation and use was conducted to determine the predominant human activities around the lagoon; an environmental diagnostic study was conducted to determine the occurrence, levels and distribution of markers; and the results of the environmental diagnostic study were compared to indicators stipulated in Brazilian legislation. Findings: Land use study revealed both urban and rural activities around the lagoon, as evidenced by the existence of residences, restaurants as well as poultry and livestock activities. The environmental diagnostic study revealed the input of human sewage (treated and raw) and runoff from animal husbandry activities. Practical implications: The information produced using anthropogenic markers showed the influence of less studied rural activities, such as livestock and poultry farming, thereby providing a more reliable environmental status compared to the use of classic indicators employed in laws issued by international and Brazilian agencies. Originality/value: The present results show that classic indicators used by environmental agencies are insufficient for an accurate diagnosis of coastal zones with multiple anthropogenic activities. Thus, the modernization of the environmental monitoring plan of the ICZM program is urgently needed for a more accurate assessment of coastal environments.